Prevalence of Dental Trauma and Their Relationship to Risk Factors among 8–15-Year-Old School Children - Kanamarlapudi Venkata Saikiran; Deepa Gurunathan; Sivakumar Nuvvula; Raghavendra Kumar Jadadoddi; Raichurkar Hemanth Kumar; Uday Chowdary Birapu (International Journal of Dentistry)
Background. Tooth injuries lead to functional, aesthetic, and psychological disorders, accompanied by the great concern of the child, the parents, and the dentist. Aim. (a) To assess the prevalence of traumatic dental injury (TDI) and its relationship to risk variables among 8–15-year-old school children in Mahbubnagar, India. (b) To collect baseline data as there are limited reports of TDI studies in South India to date. Methods. A cross-sectional study was conducted among 6643 children from 78 schools in Mahbubnagar using a multilevel random sampling method. The permanent incisors were examined according to the WHO classification using a standard oral mirror and probe. Individuals with clinical evidence of trauma were asked about the details of the injury event using a structured questionnaire. The chi-square test analyzed the distribution of all measurements in this study with a statistical significance of 0.05. Results. Among the 6643 children from the 78 schools surveyed, 9.3% experienced TDI. TDI occurred in 68% of boys, which was about twice as high in girls at 32%. The most commonly affected teeth were the maxillary central incisors. A higher number of children with an incisal overjet more significant than 3 mm had TDI than the children less than 3 mm, although this difference was not statistically significant. The lip closure incompetence was more common in children with TDI. The most frequent causes of TDI were falls, and the site of occurrence was school. Type I fractures were the most prevalent and most went untreated. Conclusion. The high level of dental trauma and the low percentage of children with trauma seeking treatment emphasize the need for greater awareness among the Mahbubnagar children.